Characteristics of Clostridioides difficile colonization in Ilamian children - Sayyadi, M.; Kouhsari, E.; Kalvandi, G.; Kazemian, H.; Ghafouri, Z.; Sadeghifard, N. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The increasing colonization with Clostridioides difficile in paediatric hospitalized population is a well known event; however, its prevalence in Iranian children has not effectively been identified yet. Objective. The objective of this study was to determine the intestinal-carriage rates of C. difficile and molecular characterization of C. difficile in the Ilamian pediatric population from May 22, 2018, until September 22, 2018. Materials and Methods. Eighty samples were obtained from 40 children aged <5 years, at day 0 of their hospitalization (N=40 samples), to determine community-associated colonization, and then at day 5 days after hospitalization (N=40 samples), to determine healthcare associated colonization. The stool samples were examined for C. difficile, and isolated strains were evaluated for production of Clostridial toxins A/B and molecular characterizations. Results. The colonization rates of C. difficile and toxigenic C. difficile were 10% (8/80) and 3.75% (3/80), respectively. Based on the age group, the intestinal-carriage rates of C. difficile were 37.5, 50, and 12.5% in children ≤ 1, 1-3, and 3-5 years old, respectively. Our findings have revealed eight distinct ribotypes. Our findings have revealed eight distinct ribotypes of C. difficile isolates. Three out of 8 (37.5%) of C. difficile isolates were considered as community-associated colonization and belonged to ribotypes 7, 8, and 9. Conclusion. Our findings suggest the need of confirmation by further epidemiological studies in Iranian children. Given that the 37.5% of cases observed were community-associated, estimates of the incidence of C. difficile infections, that include only hospitalized children, may largely underestimate the burden of disease in children.